Indonesia Public Expenditure Review 2020 : Spending for Better Results - World Bank (World Bank, Washington, DC, 2020)
Indonesia's development trajectory has been remarkable over the past 20 years, supported by macroeconomic stability and prudent fiscal management. The economy grew on average by 5.3 percent annually between 2000 and 2018, while gross national income (GNI) per capita rose six-fold from US$580 in 2000 to US$3,840 in 2018.1 As a result, Indonesia has made huge gains in poverty reduction, from 19.1 percent of the population in 2000 to 9.4 percent of the population by March 2019. Prudent fiscal management has played an important role in supporting macroeconomic stability and growth. This Public Expenditure Review (PER) aims to help identify key constraints to efficient and effective public spending and offer ways to improve the quality of spending to achieve Indonesia's development objectives. Public expenditure is a key contributor to closing Indonesia's development gaps, both through direct spending and through creating the right environment to attract private investment to help close the gaps. This PER covers the following topics: public financial management, the intergovernmental fiscal transfer system, and data for better policy making (institutional environment), and sectors: health, education and social assistance (human capital), national roads, housing, water resource management, and water supply and sanitation (infrastructure).